(untitled) (Research, Society and Development, 2024)
The species Coffea arabica L. is of great importance for the Brazilian economy, as the country is the largest producer of the species. Somatic embryogenesis is a way to propagate the species, however high rates of contamination and oxidation make the process difficult. Therefore, the objective of this work was to evaluate the antioxidant action of sodium selenate and different concentrations of carrot extract on the in vitro leaf establishment of coffee trees. The experiment was conducted at the Biotechnology and Plant Tissue Culture Laboratory at IFSULDEMINAS - Campus Muzambinho. Leaves were collected from mother plants grown in a greenhouse. Subsequently, 5 treatments were prepared with initial culture media for callus induction MI, T1 (control), T2 (10% v/v of carrot extract), T3 (0.04 g of sodium selenate), T4 (10 % v/v of carrot extract + 0.04 g sodium selenate) and T5 (16.16% v/v of carrot extract). After 30 days of inoculated explants, oxidation, fungal and bacterial contamination, yellowing and callus formation were evaluated. The means were analyzed in the SISVAR software, using the Scott Knott test at 5% probability. Treatments 3, 4 and 5 differed significantly from treatments 1 and 2, with T5 providing the lowest explant oxidation rates (37%). Tissue oxidation decreases when grown in culture medium supplemented with sodium selenate, sodium selenate + 10% v/v carrot extract and 16.16% v/v carrot extract.